PELATIHAN APLIKASI “KAHOOT” SEBAGAI MEDIA DALAM PROSES DAN EVALUASI PEMBELAJARAN BAGI PARA GURU BAHASA JERMAN DI SMA NEGERI 6 AMBON - Patresia S Apituley; Grietje H Kunu; Eldaa Crystle Wenno; Piet Soumokil (Universitas Pattimura, 2023)
The use of educational game-based media in general has not been implemented in schools in Ambon city. Even though in the digital era 4.0 educators are required to be able to use educational game-based media in the teaching and learning process. Therefore, it is necessary to provide German teachers in Ambon City at the SMA / SMK level with training on the use of technology in the learning process, one of which is the